Viability of pollen in sweet cherry (Cerasus avium) varieties of different ecogeographic origin in the Northwestern region of Russia - S. Yu. Orlova; A. V. Pavlov; V. G. Verzhuk (Труды по прикладной ботанике, генетике и селекции)
Background. Sweet cherry is an unconventional fruit crop for the Northwestern region of Russia. Identification of cultivars adapted to the conditions of the northwest requires a comprehensive study of cultivars of different ecogeographic origin and, specifically, morpho-physiological characteristics of pollen, which ensure the productivity of sweet cherries.Materials and methods. The field sweet cherry collection maintained at Pushkin and Pavlovsk Laboratories of VIR served as the material for the study carried out in 2017 at the Plant Diversity Long-Term Storage Laboratory. Twenty-four sweet cherry accessions belonging to five different groups were studied: I – Northwestern (bred at VIR); II – Central; III – Central Black Soil (all three are regions in Russia); IV – Belarus; and V – Estonia. Viability of pollen was assessed by germinating on an artificial medium with 10% sucrose and 0.6% agar. Pollen viability results were statistically processed using StatSoft Statistica 13.0 and Microsoft Excel.Results. The initial viability of pollen for almost all varieties in 2017 was low. High percentage of pollen germination was characteristic of cvs. ‘Krasnaya sladkaya’ (gr. I, 50.0%), ‘Leningradskaya rozovaya’ (gr. I, 61.8%), ‘Adelina’ (gr. III, 53.5%) and ‘Zarya Vostoka’ (gr. III, 60.3%). After storage in liquid nitrogen, the level of pollen germination increased in all cultivars of groups I and V as well as in a number of cultivars from group II (‘Raditza’, ‘Iput’, ‘Rechitsa’ and ‘Fatezh’), group III (‘Zarya Vostoka’, ‘Rondo’ and ‘Orlovskaya rozovaya’) and group IV (‘Severnaya’ and ‘Vityaz’). Pollen viability after cryopreservation significantly decreased by 8.7‑17.3% in cvs. ‘Bryanochka’ (gr. II), ‘Alebastrovaya’ (IV),’ Bryanskaya rozovaya’ (II) and ‘Adelina’ (III). Pollen viability parameters (length of pollen tubes and percentage of germinated pollen grains) positively correlated prior to immersion into liquid nitrogen from r = 0,54 (gr. III) to r = 0,76 (gr. II), while after cryopreservation, they showed weak correlation (r = 0,28) in gr. I, and strong one (r = 0,79) in group IV. In the length of pollen tubes and the level of viability, the parent cv. ‘Leningradskaya chernaya’ had practically no connection with cv. ‘Raditsa’ (r = 0.09), while with cv. ‘Meelika’ the correlation was medium negative (r = –0.49); correlations between the parent cv. ‘Krasnaya plotnaya’ and cvs. ‘Sopernitsa’, ‘Bryanochka’ and ‘Vityaz’ were medium (r = 0.57) and high (r = 0.78 and r = 0.83), respectively.Conclusion. In their level of pollen viability, the introduced sweet cherry cultivars are similar to or even exceed the cultivars native to the northwest (bred at VIR).